2021
DOI: 10.1089/hum.2020.213
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Rescue of X-Linked Retinoschisis Mouse (Rs1−/y) Retina Induces Quiescence of the Retinal Microglial Inflammatory State Following AAV8-RS1 Gene Transfer and Identifies Gene Networks Underlying Retinal Recovery

Abstract: To understand RS1 gene interaction networks in the X-linked retinoschisis (XLRS) mouse retina ( Rs1 −/y ), we analyzed the transcriptome by RNA sequencing before and after in vivo expression of exogenous retinoschisin ( RS1 ) gene delivered by AAV8. RS1 is a secreted cell adhesion protein that is critical for maintaining structural lamination and synaptic integrity of the neural retina. RS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 74 publications
(122 reference statements)
4
25
0
Order By: Relevance
“…RT-PCR analysis revealed no changes in mRNA gene expression as the cause for altered protein levels of Kv2.1 and Kv8.2. This is in line with a previous study by Vijayasarathy and colleagues, who used microarray-based genome-wide expression profiling and observed no mRNA expression differences for Kcnb1 and Kcnv2 as well as for Atp1a 3 and Atp1b2 in wildtype and retinoschisin-deficient retinae of P12 and P21 old mice [ 59 ]. Accordingly, the effect of retinoschisin-deficiency on Kv2.1 and Kv8.2 subunits should be attributed to a posttranslational process.…”
Section: Discussionsupporting
confidence: 92%
“…RT-PCR analysis revealed no changes in mRNA gene expression as the cause for altered protein levels of Kv2.1 and Kv8.2. This is in line with a previous study by Vijayasarathy and colleagues, who used microarray-based genome-wide expression profiling and observed no mRNA expression differences for Kcnb1 and Kcnv2 as well as for Atp1a 3 and Atp1b2 in wildtype and retinoschisin-deficient retinae of P12 and P21 old mice [ 59 ]. Accordingly, the effect of retinoschisin-deficiency on Kv2.1 and Kv8.2 subunits should be attributed to a posttranslational process.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, RT-PCR analysis revealed no changes in mRNA gene expression as the cause for altered protein levels. This is in line with a previous study by Vijayasarathy and colleagues, who used microarray-based genome-wide expression pro ling and observed no mRNA expression differences for Kv2.1 and Kv8.2 as well as for Atp1a3 and Atp1b2 in wildtype and retinoschisin-de cient retinae of P12 and P21 old mice [37]. Accordingly, the effect of retinoschisinde ciency on Kv2.1 and Kv8.2 subunits should be attributed to a posttranslational process.…”
Section: Discussionsupporting
confidence: 91%
“…To reveal the connections between the transcriptome and the proteome, and to discover important pathways and functional proteins, we performed a combined analysis of proteomic and published transcriptomic data [ 6 ]. The correlation analysis revealed that the proteome of RS1-KO retinas at P15 exhibited a modest correlation with the transcriptome at P12 but not with the transcriptome at P21 ( Figure 7 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Even though visual acuity may remain relatively stable in XLRS boys for years, an acceleration of vision loss due to central retinal atrophy in the fourth to fifth decade of life occurs [ 4 , 5 ]. Previous studies suggest that early interventions may alleviate the progress of XLRS in humans and animals [ 6 , 7 , 8 , 9 ]. Nevertheless, the manner in which the malfunction of the RS1 protein induces the degeneration of the inner and outer retinal neurons remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation